Contamination profiles of legacy and emerging per- and polyfluoroalkyl substances in various vegetable oils collected in Chinese markets - Wenfeng Feng; Yuepeng Lu; Yuning Hu; Jing Cheng; Ling Wang; Zhen Zhou; Yong Liang (Journal of Environmental Sciences, 2026)

Evolution of pore structure and fractal characteristics during hydrate-based CO2 sequestration in unconsolidated sediments - Zhun Zhang; Yuning Liu; Yunkai Ji; Jiaxian Wang; JinQiu Hu; Bin Fang; Wanjun Lu; Changling Liu; Fulong Ning (Chemical Engineering Journal, 2026)

Self-catalytic oxidation enables metal recovery from copper smelting flue dust - Zhiqiang Liu; Hao Du; Feifei Hu; Shaona Wang; Muneeb UI Hassan Naseer; Yuning Guo; Yeqing Lv; Biao Liu (Journal of Hazardous Materials, 2026)

Mitochondrial pathway-mediated gut cell apoptosis: A key mechanism of nitenpyram toxicity in Diaphorina citri adults - Yuning Li; Huyin Hu; Huanqian Yao; Xinyi Xie; Shuyin He; Cuiting Liu; Veeran Sethuraman; Hanhong Xu; Zhongzhen Wu; Benshui Shu (Journal of Asia-Pacific Entomology, 2026)

In-situ growth of covalent organic frameworks on 3D‐printed monolithic microfluidic chips for online analysis of naphthalene and its metabolites in cells - Qiulin Zhang; Beibei Chen; Zhen Zhou; Yong Liang; Yuning Hu; Man He (Analytica Chimica Acta, 2026)

Pressure and Permeability Evolution near Hydrate Exploitation Well During Constant-Rate Water Flooding: An Experimental Study - Yuning Liu; Yunkai Ji; Qiang Fu; Zhenyu Zhu; Zihao Wang; Gaowei Hu; Qiang Chen; Yongchao Zhang; Qingtao Bu; Yizhao Wan (Journal of Marine Science and Engineering, 2026)
Dynamic damage to the seepage characteristics of the near-well zone during natural gas hydrate exploitation is a key factor limiting production stability. There is still a lack of systematic understanding of the microscopic mechanisms underlying fine-particle migration and blockage in the near-well zone. In this study, a long sand-packed column was segmentally packed with clayey-silt sediments from the South China Sea and quartz sand to simulate the near-well reservoir and the packed layer, respectively. Long-term seepage processes in the near-well zone were simulated using water flow experiments at constant flow velocities. By combining pressure distribution monitoring with particle-size analysis, the spatiotemporal evolution of seepage characteristics in the near-well zone is revealed from both macroscopic and microscopic perspectives. Results indicate that under long-term displacement, the reservoir permeability near the injection end increased from 0.0149 mD to 0.0159 mD; the reservoir permeability near the packed layer exhibits the greatest decline, dropping from 0.0089 mD to 0.0065 mD. Combined with the particle-size analysis of the packer layer, the boundary between the reservoir and the packed layer is identified as the critical site for permeability damage in the near-well zone. Radial flow inversion shows that a reduction in wellbore radius leads to an increase in reservoir pressure, with the increase being greater the farther from wellbore. A decrease in the permeability of packed layer causes an increase in reservoir pressure, but the magnitude of the increase is consistent across different locations. It provides a theoretical basis for the optimized design of production wells.

Stepwise thermal hydrolysis and hydrothermal conversion of food waste to intensify the formation of humic acids - Xiaoyuan Zheng; Yuning Lei; Yu Hu; Zhi Ying; Bo Wang; Yuheng Feng; Binlin Dou (Bioresource Technology, 2026)

Coaxial electrospun TiO2@CuO heterojunctions with interfacial charge rearrangement for photothermal oxidation of toluene - Weimin Huang; Ke-Xin Li; Shuzhuo Bai; Shanshan Chen; Fanbin Meng; Bing Qin; Yuning Yang; Zonghui Liu; Wen-Tao Zheng; Zhun Hu (Journal of Environmental Chemical Engineering, 2026)

Aftermath of marine heatwaves on the growth and physiological performance of Sargassum fusiforme and Sargassum thunbergii - Yaoyao Chu; Fengxiao Hu; Yuning Xue; Yue Wang; Xiongwei Huang; Xiaodong Li; Kang Wang; Xianming Tang; Xinhua Chen (Marine Environmental Research, 2026)

Molecular Insights into Exoskeletal Remodeling: Transcriptomic Profiling of the Molting Cycle in the Red Swamp Crayfish Procambarus clarkii - Yunkuan Zhu; Yu Xu; Suwan Lu; Yuning Hu; Hui Xu; Jiajia Li; Hai Lin; Xuguang Li; Zhiqiang Xu (Fishes, 2026)
The molting of crustaceans is accompanied by exoskeleton reconstruction. To reveal the molecular regulation mechanism of exoskeleton remodeling, the transcriptomic profiles of the exoskeleton across the entire molting process in the red swamp crayfish Procambarus clarkii were investigated by RNA sequencing, yielding a total of 7671 differentially expressed genes (DEGs) across five different molting stages. Notably, the key DEGs were those related to cuticular exoskeleton synthesis (cuticular proteins), degradation (chitinase 2, chitinase 10) and hardening (chitin deacetylase 1), and their expression abundance varied by 10-fold or greater across the molting cycle. Analysis of Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) showed that significantly enriched pathways included the structural constituents of the cuticle, structural molecule activity, chitin binding of chitin metabolism, and hormone biosynthesis. The expression profiles of nine selected molting-related DEGs were further validated via real-time RT-PCR assays. The acquired unique temporal expression patterns involved in exoskeleton remodeling provide a preliminary insight into the regulation of gene expression during the molting cycle in the red swamp crayfish.

Telomere-to-telomere genome assembly reveals the genomic architecture of disease resistance and yield coordination in elite wheat YM33 - Guofeng Lv; Yating Wang; Heping Zhang; Yuning Shen; Wenjing Hu; Datong Liu; Mengmeng Liu; Wenna Wang; Yuwen Gao; Caixia Lan; Tongde Bie; Hongya Wu; et al. (Molecular Plant, 2026)

Research on Lateral Loading Behavior of Embedded Rock-Socketed Jacket Offshore Wind Turbines - Ronghua Zhu; Yuning Zhang; Feipeng Zou; Jiajun Hu; Zijian Tao; Yong Chen (Journal of Marine Science and Engineering, 2026)
As an innovative foundation type specifically developed for seabed conditions characterized by shallow overburden overlying bedrock, driven embedded rock-socketed jacket offshore wind turbines achieve high bearing capacity by embedding the pile tips into the bedrock. However, the mechanical behavior of this foundation system has not yet been fully clarified. In this study, based on the engineering conditions of an offshore wind power project in Fujian, a 1:100 scaled physical model test is conducted to validate Plaxis 3D finite-element model. On this basis, a parametric sensitivity analysis is conducted to investigate the influences of key geotechnical properties, pile rock-socketed depth, and geometric parameters, with the aim of elucidating the mechanisms governing the lateral loading behavior of the jacket foundation. The results show that the numerical simulations are in good agreement with the experimental measurements. Among all piles, the front-row pile exhibits the most significant displacement at the pile top at the mudline, reflecting the asymmetry in load transfer and deformation of the pile foundation system. The ultimate bearing capacity varies by about 91.7% among different bedrock types, while the influence of rock weathering degree on the lateral bearing performance of the foundation is about 4.7%. The effects of Pile rock-socketed depth and geometric parameters on the lateral bearing capacity of the foundation are approximately 15.2% and 80.8%, respectively. A critical threshold for rock-socket depth exists at about 6D (where D is the pile diameter), beyond which further improvements in embedment depth result in diminishing improvements in lateral bearing capacity.

Identification of the geographical origin of wild rice field eel (Monopterus albus) in China by stable isotopes - Weiwei Lv; Muyan Li; Yangyang Lu; Yifan Zhao; Weiwei Huang; Hang Yang; Quan Yuan; Yuning Zhang; Mingyou Li; Wei Hu; Chunxia Yao; Danhe Wang; et al. (Food Control, 2026)

An injectable triple-responsive chitosan-based hydrogel encapsulating QCT-Cu self-assembled nanoparticles accelerating diabetic wound healing via remodeling the local microenvironment - Yan Zhu; Shiyuan Yang; Jia Zhou; Zixiao Zhang; Yue Hu; Qingyu Xu; Yuning Zhou; Yuanjin Xu (Carbohydrate Polymers, 2025)

Regional Wave Spectra Prediction Method Based on Deep Learning - Yuning Liu; Rui Li; Wei Hu; Peng Ren; Chao Xu (Journal of Marine Science and Engineering, 2025)
The wave spectrum, as a key statistical feature describing wave energy distribution, is crucial for understanding wave propagation mechanisms and supporting ocean engineering applications. This study, based on ERA5 reanalysis spectrum data, proposes a model combining CNN and xLSTM for rapid gridded wave spectrum prediction over the Bohai and Yellow Seas domain. It uses 2D gridded spectrum data rather than a spectrum at specific points as input and analyzes the impact of various input factors at different time lags on wave development. The results show that incorporating water depth and mean sea level pressure significantly reduces errors. The model performs well across seasons with the seasonal spatial average root mean square error (SARMSE) of spectral energy remaining below 0.040 m2·s and RMSEs for significant wave height (SWH) and mean wave period (MWP) of 0.138 m and 1.331 s, respectively. At individual points, the spectral density bias is near zero, correlation coefficients range from 0.95 to 0.98, and the peak frequency RMSE is between 0.03 and 0.04 Hz. During a typical cold wave event, the model accurately reproduces the energy evolution and peak frequency shift. Buoy observations confirm that the model effectively tracks significant wave height trends under varying conditions. Moreover, applying a frequency-weighted loss function enhances the model’s ability to capture high-frequency spectral components, further improving prediction accuracy. Overall, the proposed method shows strong performance in spectrum prediction and provides a valuable approach for regional wave spectrum modeling.

The combination of microscopic and metabarcoding analyses revealed a high diversity of algal bloom species in the Taiwan Strait - Yuning Zhang; Lanping Lin; Hu Zheng; Changliang Xie; Junning Gu; Zhaohui Wang; Jiangang Zhao (Marine Pollution Bulletin, 2025)

Corrigendum to “Trace-elements driven up-regulation of secreted proteases expression in the human-pathogenic fungus Trichophyton rubrum” [J. Trace Elem. Med. Biol. 87 (2025) 127580] - Oliver Blechert; Shanyu Lan; Shuzhen Xiong; Yuning Zou; Peicong Li; Jiewei Hu; Jiayuan Li; Ping Zhan (Journal of Trace Elements in Medicine and Biology, 2025)

Single-cell RNA sequencing reveals the heterogeneity of hepatopancreas cells and their association with gonadal development in the red swamp crayfish Procambarus clarkii - Lin Du; Yuning Hu; Siyu Lu; Xuguang Li; Jiajia Li; Hai Lin; Jiaxin Yang; Yu Xu; Zhiqiang Xu (Aquaculture, 2025)

Dissolved organic matter mitigates the toxicity of silver nanoparticles to freshwater algae: Effects on oxidative stress and membrane function - Jilai Zhang; Chenglei Hu; Ming Jiang; Qianqian Xiang; Sheng Wang; Youbo Su; Naiming Zhang; Zhihao Si; Yuning Mu; Ran Yang (Environmental Pollution, 2025)

Trace-elements driven up-regulation of secreted proteases expression in the human-pathogenic fungus Trichophyton rubrum - Oliver Blechert; Shanyu Lan; Shuzhen Xiong; Yuning Zou; Peicong Li; Jiewei Hu; Jiayuan Li; Ping Zhan (Journal of Trace Elements in Medicine and Biology, 2025)

Epithelial-mesenchymal transition during the growth and involution of the prostate gland in wild ground squirrels (Spermophilus dauricus) - Pengyu Chen; Xinyue Hu; Qingjing Gao; Yue Zhou; Wenjing Lu; Xingye Zhang; Maria Daniela Artigas Ramirez; Yingying Han; Zhengrong Yuan; Yuning Liu; Qiang Weng; Haolin Zhang (Animal Reproduction Science, 2025)

On the Nearshore Significant Wave Height Inversion from Video Images Based on Deep Learning - Chao Xu; Rui Li; Wei Hu; Peng Ren; Yanchen Song; Haoqiang Tian; Zhiyong Wang; Weizhen Xu; Yuning Liu (Journal of Marine Science and Engineering, 2024)
Accurate observation of nearshore waves is crucial for coastal safety. In this study, the feasibility of extracting wave information from wave video images captured by shore-based cameras using deep learning methods was explored, focusing on inverting nearshore significant wave height (SWH) from instantaneous wave video images. The accuracy of deep learning models in classifying wind wave and swell wave images was investigated, providing reliable classification results for SWH inversion research. A classification network named ResNet-SW for wave types with improved ResNet was proposed. On this basis, the impact of instantaneous wave images, meteorological factors, and oceanographic factors on SWH inversion was evaluated, and an inversion network named Inversion-Net for SWH that integrates multiple factors was proposed. The inversion performance was significantly enhanced by the specialized models for wind wave and swell. Additionally, the inversion accuracy and stability were further enhanced by improving the loss function of Inversion-Net. Ultimately, time series inversion results were synthesized from the outputs of multiple models; the final inversion results yielded a mean absolute error of 0.04 m and a mean absolute percentage error of 8.52%. Despite certain limitations, this method can still serve as a useful alternative for wave observation.

Identification of QTLs associated with very-long chain fatty acid (VLCFA) content via linkage mapping and BSA-seq in peanut - Xiaomeng Xue; Jianguo Li; Jie Wu; Meiling Hu; Nian Liu; Liying Yan; Yuning Chen; Xin Wang; Yanping Kang; Zhihui Wang; Huifang Jiang; Yong Lei; et al. (Theoretical and Applied Genetics, 2024)

Semantic segmentation of urban land classes using a multi-scale dataset - Qian Wang; Chunhua Hu; Hanzhao Wang; Rui Wang; Yuning Xie; Yuankun Zhao (International Journal of Remote Sensing, 2024)

Effects of 5-Azacytidine (AZA) on the Growth, Antioxidant Activities and Germination of Pellicle Cysts of Scrippsiella acuminata (Dinophyceae) - Zhaohui Wang; Jianneng Zhang; Tao Tang; Yuning Zhang; Ren Hu (Journal of Ocean University of China, 2023)

Hydrochar coupled with iodide for efficient photodegradation of perfluorooctanoic acid and perfluorooctane sulfonic acid under ultraviolet light - Yuning Hu; Yuhang Zhan; Cuiyun Wei; Fengjie Chen; Jing Cheng; Yunxiang Shen; Zhen Zhou; Ling Wang; Yong Liang (Science of The Total Environment, 2023)

The Responses of Sediment Bacterial Communities in Chinese Mitten Crab (Eriocheir sinensis) Culture Ponds to Changes in Physicochemical Properties Caused by Sediment Improvement - Tianheng Gao; Nannan Li; Wenlei Xue; Yuning Hu; Hai Lin (Fishes, 2023)
The interaction between nutrients, heavy metals, and sediment bacterial communities play a key role in the health of crabs and the biogeochemical cycles of aquaculture systems. However, the effects of sediment improvement activities in crab culture on nutrients and heavy metals and the response of bacterial communities to the relevant changes are unclear. In this study, 24 water and sediment samples were collected from two aquaculture sites (total of 12 ponds, 6 at each site). High-throughput sequencing was used to determine the structure of the bacterial community and the diversity in water and sediment samples. The relationship between nutrients, heavy metals, and bacterial communities and the changes of the three before and after the improvement of the sediment were analyzed. The results showed that Proteobacteria, Bacteroidetes, Acidobacteria, Chloroflexi, and Firmicutes were predominant at the phylum level of sediment. Sediment improvement has an effect on NH4+-N, sulfide, total organic carbon (TOC), and heavy metals in sediments to varying degrees. In addition, redundancy analysis found that NH4+-N, NO3−-N, TP, and heavy metals were key drivers in crab culture pond sediments. The results of functional prediction showed that carbon, nitrogen, and sulfur metabolism were the dominant processes in the two crab farming areas. Overall, changes in nutrients and heavy metals caused by sediment improvement further affected the structure and function of bacterial communities and may affect biogeochemical cycles. Our study has deepened the understanding of the effects of sediment improvement on nutrients, heavy metals, and bacterial communities in crab culture ponds.

Distribution of Dinoflagellate Cysts in Surface Sediments From the Qingdao Coast, the Yellow Sea, China: The Potential Risk of Harmful Algal Blooms - Zhaohui Wang; Yuning Zhang; Mingdan Lei; Shuanghui Ji; Jiazhuo Chen; Hu Zheng; Yali Tang; Ren Hu (Frontiers in Marine Science, 2022)
Surface sediments were collected from three sea areas of the Qingdao coast, the Yellow Sea, China, namely, the inner Jiaozhou Bay, the Laoshan coast, and the Amphioxus Reserve area in November to December 2017. Dinoflagellate cysts were observed in the sediments, focusing on the distribution of toxic and harmful species. Contents of biogenic elements were analyzed to reveal their relationships to cysts. A total of 32 cyst taxa were identified, including 23 autotrophic and 9 heterotrophic taxa. Cyst concentrations ranged from 83.3 to 346.5 cysts/g D Wt with an average of 210.7 cysts/g D Wt. Generally, cysts of autotrophic dinoflagellates dominated in sediments from the Qingdao coast with proportions of 41.05%–90.25%. There were no dominant group in cyst assemblages; cysts of Protoperidiniaceae, Suessiales, and Calciodinelloideae showed similar contributions. Cyst assemblages were quite different in the inner Jiaozhou Bay reflected by the lower species richness, diversity, and cyst concentration. Results from the redundancy analysis (RDA) demonstrated the influence of biogenic elements on cyst assemblages, which explained well why the three sea areas with different degrees of human activities showed different dinocyst storages. Notably, 17 harmful algal bloom (HAB) dinoflagellate cysts were identified in this study, including cysts of those producing toxins that may damage human health and marine animals. Some of these cysts occurred widely and dominantly in this study, such as cysts of Gonyaulax spinifera , Azadinium trinitatum , Scrippsiella acuminata , and Biecheleria halophila , suggesting the potential risk of HABs in the Qingdao coastal area.

An improved space colonization algorithm with DBSCAN clustering for a single tree skeleton extraction - Yifan Xu; Chunhua Hu; Yuning Xie (International Journal of Remote Sensing, 2022)

Serum Iron and Ferritin Levels Are Correlated with Complement C3 - Shuang Wen; Yeqin Sha; Yinling Li; Zhilian Rui; Chenhong Si; Yuning Zhou; Fengfeng Yan; Bicheng Wang; Jingming Hu; Xu Han; Dongyan Shi (Biological Trace Element Research, 2021)

Genetic diversity analysis for narrow-leafed lupin (Lupinus angustifolius L.) by SSR markers - Yishan Ji; Rong Liu; Jinguo Hu; Yuning Huang; Dong Wang; Guan Li; Md. Mosiur Rahman; Hongyan Zhang; Chenyu Wang; Mengwei Li; Tao Yang; Xuxiao Zong (Molecular Biology Reports, 2020)

Review of Chinese atmospheric science research over the past 70 years: Synoptic meteorology - Zhiyong Meng; Fuqing Zhang; Dehai Luo; Zhemin Tan; Juan Fang; Jianhua Sun; Xueshun Shen; Yunji Zhang; Shuguang Wang; Wei Han; Kun Zhao; Lei Zhu; et al. (Science China Earth Sciences, 2019)

Chemical composition, antioxidant and cytoprotective activities of lotus receptacle - Weicheng Hu; Gongcheng Wang; Ting Shen; Yuning Wang; Boran Hu; Xinfeng Wang; Lei Wu; Pengxia Li; Lilian Ji (Horticulture, Environment, and Biotechnology, 2015)

Control of postharvest soft rot caused by Erwinia carotovora of vegetables by a strain of Bacillus amyloliquefaciens and its potential modes of action - Yancun Zhao; Pengxia Li; Kaihong Huang; Yuning Wang; Huali Hu; Ya Sun (World Journal of Microbiology and Biotechnology, 2013)